A sequência espectral de Serre - Martins, Matheus Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Nessa dissertação, estudamos a construção da sequência espectral de Serre associada a uma fibração. Para culminar em sua formulação, passamos por tópicos da Topologia Algébrica taiscomo álgebra homológica, grupos de homotopia, grupos de homologia e de cohomologia, sis-temas de coeficientes locais e grupos de homologia e cohomologia com coeficientes locais.

In the present dissertation, we study the construction of the Serre spectral sequence associated to a fibration. In order to get its formulation, we first developed topics in Algebraic Topology such as homological algebra, homotopy groups, homology and cohomology groups, system of local coefficients, and homology and cohomology groups with local coefficients.
The Serre Spectral Sequence
Keywords: Cohomologia de grupos; Fibração; Sequência espectral (Matematica); Topologia algébrica; Algebraic topology; Cohomology operations; Spectral sequence; Fibration